Pengaruh Green Product Dan Word Of Mouth (Wom) Di Era Eco-Friendly Terhadap Keputusan Pembelian Melalui Minat Beli Sebagai Variabel Intervening Pada Konsumen Fore Coffee Surabaya - Lathifah, Nur Aini; Atho`illah, Akhmad Yunan (LAN TABUR : Jurnal Ekonomi Syariah, 2023)
Environmental issues are currently starting to be widely discussed, which can also be a consideration for businesses to adopt as part of their operations. One of them is green products which have been used in several business fields and can generate positive word of mouth compared to conventional products. This research aims to determine the influence of green products and word of mouth (WOM) on decisions with purchase intention as an intervening variable for Fore Coffee Surabaya consumers. The population of this research is all consumers who make purchases at Fore Surabaya. The number of respondents to this research was 165 who used a non-probability sampling type with a purposive sampling technique. The results of this research show that: (1) green products have a significant effect on buying interest, (2) word of mouth (WOM) has a significant effect on buying interest, (3) green products have no effect on purchasing decisions, (4) word of mouth (WOM) has a significant effect on purchasing decisions, (5) buying interest has a significant effect on purchasing decisions, (6) green products have a significant effect on purchasing decisions through buying interest as mediation, and (7) word of mouth (WOM) has a significant effect on decisions purchase through purchase interest as mediation.